The Pivotal Role of Host Organizations in Enhancing Mentoring in Internal Medicine: A Scoping Review - Elisha Wan Ying Chia; Kuang Teck Tay; Shiwei Xiao; Yao Hao Teo; Yun Ting Ong; Min Chiam; Ying Pin Toh; Stephen Mason; Annelissa Mien Chew Chin; Lalit Kumar Radha Krishna (Journal of Medical Education and Curricular Development, 2020)
In undergraduate and postgraduate medical education, mentoring offers personalized training and plays a key role in continuing medical education and the professional development of healthcare professionals. However, poor structuring of the mentoring process has been attributed to failings of the host organization and, as such, we have conducted a scoping review on the role of the host organization in mentoring programs. Guided by Levac et al’s methodological framework and a combination of thematic and content analysis, this scoping review identifies their “defining” and secondary roles. Whilst the “defining” role of the host is to set standards, nurture, and oversee the mentoring processes and relationships, the secondary roles comprise of supporting patient care and specific responsibilities toward the mentee, mentor, program, and organization itself. Critically, striking a balance between structure and flexibility within the program is important to ensure consistency in the mentoring approach whilst accounting for the changing needs and goals of the mentees and mentors.